Climate Change Salience, Economic Insecurity, and Support for Mitigation Policies - David W. Johnston; Rachel Knott; Silvia Mendolia (Institute of Labor Economics (IZA), 2022)
Many people remain opposed to climate change mitigation policies. This opposition is an obstacle to policy action and, therefore, important to understand. We explore how unusually high temperatures (heat waves), which observably increase the salience of climate change-related issues, affect people's support for policies to reduce emissions. We additionally test whether this relationship is moderated by economic status and employment conditions. By linking local temperature observations to attitudes collected in large U.K. surveys, we find that unusually hot weather caused significant reductions in support in 2012-2013, a high-unemployment period, but not in 2018-2019, a low-unemployment period. The negative effects in 2012-2013 were driven by people working in carbon-intensive industries and people who felt economically insecure. Overall, these findings suggest that economically vulnerable groups can respond negatively to the promotion of climate change mitigation policies, but that this negativity is mutable.
Keywords: D83; H23; Q54; Q58; 330; climate change; attitudes; economic insecurity; employment